2007
DOI: 10.1148/rg.27si075511
|View full text |Cite
|
Sign up to set email alerts
|

Breast Tomosynthesis: Present Considerations and Future Applications

Abstract: Mammography is an effective imaging tool for detecting breast cancer at an early stage and is the only screening modality proved to reduce mortality from breast cancer. However, the overlap of tissues depicted on mammograms may create significant obstacles to the detection and diagnosis of abnormalities. Diagnostic testing initiated because of a questionable result at screening mammography frequently causes patients unnecessary anxiety and incurs increased medical costs. Breast tomosynthesis, a new tool that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
148
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(153 citation statements)
references
References 21 publications
2
148
2
1
Order By: Relevance
“…This technique allows the generation of 3D data and resolves the problem of tissue overlap. It was reported that the advantage of this technique is to improve the diagnostic accuracy by better visibility of the low contrast features that are hard to depict in conventional 2DMMG due to breast tissue overlap for Western women (Gur, 2007;Park et al, 2007;Michell et al, 2012;Alakhras et al, 2013;Houssami et al, 2013;Skaane et al, 2013;Zuley et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This technique allows the generation of 3D data and resolves the problem of tissue overlap. It was reported that the advantage of this technique is to improve the diagnostic accuracy by better visibility of the low contrast features that are hard to depict in conventional 2DMMG due to breast tissue overlap for Western women (Gur, 2007;Park et al, 2007;Michell et al, 2012;Alakhras et al, 2013;Houssami et al, 2013;Skaane et al, 2013;Zuley et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The technique has previously been evaluated in mainly chest radiography [8][9][10] and mammography [11], but has also been applied in abdominal imaging [12] and in musculoskeletal radiography. In a pilot study on scaphoid fracture detection at the two-weeks' follow-up of suspect occult fracture [13], radiography detected one scaphoid waist fracture not detected at radiography at the time of the trauma, while tomosynthesis detected this fracture and two additional fractures, not seen with radiography.…”
Section: Introductionmentioning
confidence: 99%
“…With traditional mammography technique, the object is projected onto the detector or film to generate the 2D projection image of the breast. Superimposed objects on the projection images, caused by overlapped anatomical structures, bring limitations to mammography [3,4], such as 20 % false-negative rates and high recall rates, which may result in unnecessary anxiety to the patients and increase the medical costs.…”
Section: Introductionmentioning
confidence: 99%
“…Since 3D slice images of the breast can be partially reconstructed based on a few limited angle projection images, DBT has the potentials to help decrease recall rates, improve the accuracy of breast cancer detection, and therefore reduce the number of women who die from such cancer [4].…”
Section: Introductionmentioning
confidence: 99%